Chimeric receptor-binding domain vaccine design and sequential immunization enhanced broadly neutralizing antibody responses against COVID-19 - Yang, Xiao; Tang, Xin; Sun, Ying; Xi, Hualong; Peng, Wei; Yan, Lu; Teng, Wenjing; Zang, Yang; Jiang, Chunlai (Frontiers in Immunology, 2025)
IntroductionVaccines developed using modified messenger RNA (mRNA) technology show robust efficacy against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in humans. However, viral evolution in human and non-human hosts may compromise vaccine performance due to the emergence of new variants with strong immune-escape abilities. Therefore, a coronavirus disease 2019 (COVID-19) vaccine that induces high levels of broadly neutralizing antibodies (bnAbs) and responds quickly to viral mutations is urgently required.MethodsHere, we designed a bivalent mRNA vaccine, RBDco, based on the variant of concern (VOC) spike (S) protein receptor-binding domain (RBD) chimeric from different lineages fused with Fc fragments.ResultsIn mice and non-human primates, RBDco effectively induced neutralizing antibodies against several pseudoviruses, including the possible epidemic variants XBB.1, XBB.1.9.1, and EA.1 pseudoviruses. In mice, RBDco induced bnAbs against 11 SARS-CoV-2 variant pseudoviruses from different lineages. The neutralizing antibody titers against the prototype D614G and the epidemic variant XBB.1.16 were 19666 and 13274, respectively. RBDco induced mice secrete interferon-γ (IFN-γ) under the stimulation of RBD proteins of SARS-CoV-2 variants. In the mouse challenge model, RBDco treatment led to a 10-fold reduction in the viral load in the lungs of mice after the challenge. These results suggest that RBDco can induce a bnAb response and cellular immune response in animals, thereby preventing the occurrence of COVID-19. Furthermore, the sequential immunization results showed an improved neutralizing antibody titer in RBDco-boosted groups relative to the inactivated group. Enhanced differentiation of memory T cells was observed in the RBDco-boosted group.DiscussionOverall, RBDco can induce bnAbs in animals via chimeric RBDs with the SARS-CoV-2 VOC in different lineages and is a candidate for mRNA vaccine for a rapid response to viral mutations.